Studi Perbandingan Antara Jump Shoot dengan Shooting ditempat Menggunakan Dua Tangan diatas Kepala dalam Permainan Bola Basket Pada Siswa Putra SMA Tarvid Ende - Mbabho, Finsensius (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2024)
This research is entitled Comparative Study between Jump Shoot and Shooting in Place Using Two Hands Above the Head in Basketball Games among Male Students at Tarvid Ende High School in 2023. The method used is Expost Facto research, Expost facto is a research method where manipulation (treatment) of the independent variable has been carried out. happened previously so that the research does not need to provide further treatment, just the effect on the dependent variable. The researcher can draw the following conclusion: "There is a difference between jump shooting and shooting on the spot using two hands above the head in the basketball game for class X boys at Tarvid Ende High School in 2023." (3.918 > 2.069) with degrees of freedom (db) = (N-1) = 24 – 1 = 23 and at a significance level of 5%. Thus, the t-test value obtained in the research is significant, so the null hypothesis (Ho) is reads: "There is no comparison between jumpshooting and shooting on the spot using two hands above the head in a basketball game for class in place of using two hands above the head in a basketball game for class X male students at Tarvid Ende High School in 2023 "accepted.